Journal of Human Sport and Exercise - 2018 - Spring Conferences of Sports Science 2018
DOI: 10.14198/jhse.2018.13.proc2.01
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and motivation in athletes of different modalities

Abstract: This research study aims at analysing motivational climate and emotional intelligence in athletes of different categories of sports according to their gender and category of sport practised, on a sample of 372 athletes aged between 18 and 50, evaluated by means of the Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2), the Schutte Self Report Inventory (SSRI) questionnaire on emotional intelligence in sports and a self-registration sheet which measured the variables of gender and category of sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
(28 reference statements)
2
18
0
1
Order By: Relevance
“…The secondary aim of the present study was to describe the possible relationship between EI and sports experience in male and female athletes. The differences found between levels of EI is supported by previous studies ( Laborde et al, 2014 , 2016b , 2017 ; Castro-Sánchez et al, 2018a , b ), and they encourage further study into the possible relationships between EI and sports experience manifested themselves in the subgroups (male and female athletes). Female athletes achieved higher scores in EA, which is in line with the findings of Merino et al (2020) in combat sports.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The secondary aim of the present study was to describe the possible relationship between EI and sports experience in male and female athletes. The differences found between levels of EI is supported by previous studies ( Laborde et al, 2014 , 2016b , 2017 ; Castro-Sánchez et al, 2018a , b ), and they encourage further study into the possible relationships between EI and sports experience manifested themselves in the subgroups (male and female athletes). Female athletes achieved higher scores in EA, which is in line with the findings of Merino et al (2020) in combat sports.…”
Section: Discussionsupporting
confidence: 76%
“…The type of sport, time spent practicing (frequency days/week, years of practice), the number of different sports practiced, and the highest competitive level achieved are all characteristics of sports experience that may be related to EI. In contrast, some studies showed different results of EI within gender in the sport context ( Laborde et al, 2014 ; Szabo and Urban, 2014 ; Castro-Sánchez et al, 2018a ; Merino et al, 2019 , Merino et al, 2020 ). Thus, this research aimed to analyze the association between different variables related to sports experience [type of sport (individual, team, outdoor, or combat), the number of years practicing sports, the training frequency, the number of different practiced sports and the level of competition achieved (not competitive, local/regional, or national/international)] and EI dimensions (EA, EC, and ER) of undergraduate athletes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the studies consulted, it is appreciated how the practice of physical activity and sports offer many satisfactions, in exchange for many efforts. Physical activity incorporates relaxation, offering an opportunity to face challenges, as well as a way of collaboration and motivation in a team or a competition with oneself [19,20]. IE and physical activity are intimately related, to such an extent that many of the techniques of relaxation, concentration, visualization are shared in an increasing number of clubs, federations, and even coaches are hiring more professionals to implement these techniques, aiming to improve the performance of athletes [21].…”
Section: Introductionmentioning
confidence: 99%